Lithuania : Financial Sector Assessment Program Update-Technical Note-IOSCO Objectives and Principles of Securities Regulation Assessment. (IMF Staff Country Reports; Country Report, 2008)
This Technical Note provides an analysis of the evolution of the observance of the International Organization of Securities Comteams (IOSCO) objectives and principles of securities by the Lithuania Securities Commission (LSC). The analysis focuses on the Core Principles for which there have been changes in observance since the IOSCO Detailed Assessment was carried out in the framework of the Lithuania Financial Sector Assessment Program (FSAP) in 2001. The analysis is presented principle by principle or for a group of principles depending on the nature of the findings by comparison with the Detailed Assessment of 2001.